Future HRM challenges for multinational firms in Eastern and Central Europe - Horwitz, Frank Martin (Cranfield University, 2011)
This article identifies and evaluates human resource challenges for multinational companies in transitional economies in Central and Eastern European countries (CEEC). The nature of transitional economies and HRM in post-socialist societies presents a range of issues. These pertain to the lingering effects of the previous institutional environment and state directed political economies which retain influence on the type of HRM practices adopted. Challenges of talent attraction and retention, remuneration systems, diversity and cross-cultural management are considered.
Keywords: human resource management; multinationals; Central Europe; Eastern Europe